FACTORS INFLUENCING THE NUTRITION STATUS OF CHILDREN UNDER 5 YEARS AT THE NUTRITION AND PEADIATRIC WARD IN IGANGA HOSPITAL. - ORUMI , EMMANUEL; NAMUTEBI , FLORENCE (Student’s Journal of Health Research Africa, 2024)
Introduction: Objectives of the study:to assess the factors influencing nutrition status among children under 5 years at the nutrition and paediatric wards in Iganga General Hospital. The specific objectives were to assess the level of knowledge of caregivers of children, to assess the practices of caregivers of children and to find out the maternal factors; influencing nutrition status among children under 5 years at the nutrition and paediatric wards in Iganga General Hospital. Methodology: A cross sectional descriptive study design was used, using both qualitative and quantitative approaches at the nutrition and paediatric wards in Iganga General Hospital. The researcher conveniently sampled on 100 respondents from 6th January 2023 to 25th January 2023. Data collection was by using self-administered questionnaires which were filled and later analyzed using tables, graphs and pie charts. Results: Out of the 100 respondents. Majority; 89(89%) knew the importance of exclusive breastfeeding to the children for at least 6 months. Majority; 79(79%) practiced appropriate complimentary feeding while 21(21%) did not. Majority; maternal factors like age and education levels had some effect on the factors that influence on the nutrition status of the under 5years children in Iganga general hospital. Conclusion: The study showed that despite the caretakers having knowledge of exclusive breastfeeding and complementary feeding of the children, a number of them adhere not to the practices and application of the knowledge and this was affiliated to the limited resources to do so. The study further identified that maternal age, marital status, education level and occupation had a significant influence on the nutrition status of the children under 5 years. Recommendation: There is need for the caretakers to adhere to the practices and knowledge acquired in order to effect results concerning the improvement of the nutrition status of children